Long-Standing Remission After Tildrakizumab Treatment in a Case of Refractory Type I Pityriasis Rubra Pilaris in a Breast Cancer Patient - Di Lernia V; Peccerillo F (Dove Medical Press, 2024)
Vito Di Lernia, Francesca Peccerillo Dermatology Unit, Azienda Unità Sanitaria Locale- IRCCS di Reggio Emilia, Reggio Emilia, ItalyCorrespondence: Vito Di Lernia, Dermatology Unit, Arcispedale Santa Maria Nuova, Azienda USL-IRCCS di Reggio Emilia, Viale Risorgimento 80, Reggio Emilia, 42123, Italy, Tel +39 522 296873, Email vito.dilernia@ausl.re.itAbstract: Pityriasis rubra pilaris (PRP) is a rare chronic inflammatory skin disease characterised by follicular keratotic papules and perifollicular erythema coalescing into orange-red scaly plaques, and palmoplantar keratoderma. Characteristic islands of sparing are usually observed. A standardised therapeutic approach is lacking owing to the infrequent occurrence of this disease. However, anti-interleukin (IL)-17 and anti-IL-23 therapies have recently emerged as effective therapies in patients affected by PRP, with improvements in severity scores, change in severity of erythema, scaling, and thickness of lesions. Here, we report a 43-year old, female breast cancer who developed severe refractory PRP, which greatly impacted her quality of life. The patient experienced a marked improvement after treatment with tildrakizumab. Treatment was stopped after one year, and the three-year follow-up did not show relapse. In conclusion, 52- week treatment with tildrakizumab, an IL-23 antagonist, proved to be a favourable treatment option for PRP, leading to good patient adherence, improvement in quality of life, and long-term follow-up without relapse.Keywords: pityriasis rubra pilaris, treatment, tildrakizumab, breast cancer